The Malay world polity system : a brief introduction / Nasrudin Mohammed - Mohammed, Nasrudin (Universiti Teknologi MARA, Shah Alam, 2004)
Apart from the local ethnic, the Malays and aborigines (orang asli), Malaysia is a fairly small country with a population of Chinese and Indians whose ancestors, during end of 1700s, came to this country as immigrants from China and South and North India.[i] As such, Malaysia identifies itself as being a multi-cultural, multi-religious, and multi-linguistic society.